HORTICULTURAL LANDSCAPES AND FOOD CULTURE IN GUATEMALA - González-Cabañas, Alma Amalia (Revista Geográfica de América Central., 2013)
The term landscape is linked to a people´s cultural expression in their land. Therefore technolo-gical changes become visible through the impression they leave on the landscape and changes in people´s practices and food habits. The field investigation was carried out by the author during 2008 and 2009 in the indigenous communities of Almolonga and Zunil in the county of Quetzalte-nango in Guatemala. These communities are mostly involved in agriculture. The concept of landscape allows an approximation of geographical space as well as the evolution of technical and organizational methods in the field of indigenous subsistence agriculture. Horti-cultural cultivation in this area, with particularly favorable conditions due to its volcanic soils and availability of water, has become exposed to the market and techniques requiring ever more inten-sive use of resources. This investigation demonstrates the difficulties facing subsistence farmers exposed to intensive production systems. On the one hand, natural resources deteriorate and on the other, social cohesion weakens. Rural productive land becomes important when demonstrating the link between this and food culture. The loss of a landscape is no more than a technical and production change as well as signaling a lack of marks of identity, for example food. One turns to the renewal of food practices and habits by marking food as a completely social act that highlights social inequalities caused by the current global agro-food system, something that is questioned throughout the article.